ANALISIS RESPONS DARI TENSION LEG PLATFORM YANG DIBERI CONTROL ACTIF - Rubiana Widarda, Dina
In order to provide resistance to displacement response due to external load such as wave, current or wind of the Tension Leg Platform structure, the used of active control is proposed in this thesis. The additional tensile force is applied to the tether for reducing the displacement response as an active control force in Tension Leg Platform structure. The magnitude of control force is limited by allowable stressed of the tether. Numerical analysis with state space method, modal superposition method and Wilson 9 method is applied to the dynamic analysis of the structure. The simulation of displacement response shown that in Tension Leg Platform structure can be well controlled with optimal control method. The biggest reduction of structure displacement response is in surge direction